1028 neonatal electrocardiograms. Issue 6 (June 1979) - Jones, R W; Sharp, C; Rabb, L R; Lambert, B R; Chamberlain, D A
Abstract : Electrocardiograms were recorded from 1028 (99.4%) of 1034 consecutively born babies on the 1st or 2nd day of life. Abnormalities of cardiac rhythm or conduction were found in 49 (4.8%) babies. 17 babies had single or multiple premature beats during the recordings, and 7 babies showed sudden increases in R-R interval possibly due to sinoatrial node dysfunction. One baby had sinus or junctional bradycardia of less than 80 beats/min. One baby had an incessant reciprocating tachycardia and subsequently required digoxin for heart failure. Continuous 24-hour ECG monitoring in 25 babies with abnormalities of the screening ECG, and 25 babies without such abnormalities, failed to show any additional tachyarrhythmias or bradyarrhythmias warranting treatment. In view of the uncertain clinical significance of many neonatal arrhythmias and cardiac conduction disorders, more information concerning their natural history and relationship to sudden unexpected death in infancy is needed before recommending that neonatal ECG screening be generally adopted.